CO2 emission and O2 uptake of soil under different systems - Almeida, Risely Ferraz [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The soil O2 and CO2 concentration are the two most important gases related to soil microorganisms. Thus, this thesis was developed to observe the concentration and relationship between carbon dioxide (CO2) and oxygen (O2) under different residue systems. For that, we run two soil experiments in Brazil and the USA, respectively. The first experiment was developed to examine the relationship between CO2 and O2 using soil moisture and O2 as a soil respiration predictor in a sugarcane area under different managements of residues (mechanical harvesting - GH versus straw burning - BH). Therefore, the first experimental results are described in the Chapter 2 and entitled “Use of O2 uptake as an index of CO2 respiration in sugarcane areas under different managements”. We run the second soil experiment measuring biochar’s impact on CO2 production or sorption and O2 uptake in amended soils. Thus, we studied three soil types (Rosemount - RM; Potting soil Sunshine - PS; and UM) and five different biochars (Pine chip biochar - ICM; Royal Oak hardwood lump charcoal - RO; Accurel activated charcoal - AAC; Bamboo - B; and Macadamia nut - MC) and control treatment (Soil without biochar). Consequently, the results are described in the Chapter 3 and entitled “How O2 uptake can help us understand the CO2 sorption processes by biochar?”. Thus, we can conclude with our results that the concentration and relationship between FCO2 and FO2 depend on different systems and soil conditions, for example: soil crop residue managements, soil moisture and use of biochar. The FO2 is positively correlated with FCO2 at biological condition with respiratory quotient (RQ) values close to 1.0. Moreover, we can observe that RQ values higher than 1 are results of soil–gas exchange fluxes after precipitation or higher available on O2. Thus, the FO2 can be used as an index for categorizing the source of FCO2 respiration. To finish, we can observe that the biochar can be used to sequester CO2 from the atmosphere by the absence of biological activities in a short period of time. However, we believe that more study should be developed to elucidate the CO2 and O2 sorption by biochars and their reactions (biological and/or chemical) when added biochar in soil.

O oxigênio (O2) e o dióxido de carbono (CO2) no solo são os dois principais gases relacionados com a atividade dos microorganismos no solo. Assim, esta tese foi desenvolvida para observar a concentração e a relação entre a concentração do CO2 e O2 sob diferentes sistemas de resíduos. Para isso, realizamos dois experimentos de solo no Brasil e nos EUA, respectivamente. O primeiro experimento foi desenvolvido para examinar a relação entre fluxo de CO2 (FCO2) e o fluxo de O2 (FO2) usando a umidade do solo e o O2 como um predictor da respiração do solo em uma área de cana-de-açúcar sob diferentes manejos de resíduos (colheita mecânica - GH versus colheita queimada – BH). Portanto, os resultados do primeiro experimento estão descritos no Capítulo 2 e sendo intitulado de "Uso da captura de O2 como índice de respiração de CO2 em áreas de cana-de-açúcar sob diferentes manejos". O segundo experimento do solo observou o impacto do biochar na emissão ou sorção de CO2 e O2 nos solos. Assim, foram estudados três tipos de solos (Rosemount - RM, Potting Sol Sunshine - PS e UM), cinco biochars diferentes (biochar de chip de pinho - ICM, biochar de Carvalho Oak Royal - RO, biochar Acurel ativado - AAC, biochar de Bambu - B; biochar de Macadâmia - MC) e o tratamento controle (solo sem biochar). Consequentemente, os resultados foram descritos no Capítulo 3 e intitulado "Como a captura de O2 pode nos ajudar a entender os processos de sorção de CO2 via biochar?". Assim, nós podemos concluir com os nossos resultados que a concentração e relação entre FCO2 e FO2 dependem dos diferentes sistemas e condições dos solos estudados, tais como: manejo de resíduos de culturas do solo, umidade do solo e uso de biochar. O FO2 está positivamente correlacionado com o FCO2 via atividade biológica e com valores de coeficientes respiratório (RQ) próximos de 1,0. Além disso, podemos observar que valores de RQ maiores que 1 são resultados dos fluxos de troca solo-gás após precipitação ou maior disponibilidade de O2 no meio. Assim, o FO2 pode ser utilizado como um índice para categorizar uma fonte de respiração de CO2. Para concluir, o biochar pode ser utilizado para sequestrar CO2 da atmosfera em curto período de tempo. No entanto, acreditamos que mais estudos devem ser desenvolvidos para elucidar a sorção de CO2 e O2 pelo biochar e suas reações (biológicas e/ou químicas) quando adicionado biochar no solo.
Emissão de CO2 e captura de O2 do solo em diferentes sistemas
Keywords: Respiratory quotient; Biological respiration; Soil crop residue; Biochar